The Effect of Muslim Community Acceptance of Sexual Consent on the Effectiveness of the Minister of Education, Culture, Research and Technology Regulation Number 30 of 2021 - Alfath, Tahegga Primananda; Rahmawati, Winda; Wulandari, Safira; Prehatiningsih, Febry Dwi; Muharatulloh, Edshafa (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2022)
This study aims to analyze the effect of Muslim community acceptance on the effectiveness of the Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 (Permendikbudristek No. 30 of 2021). The presence of the phrase "sexual consent" hereinafter referred to as sexual consent in Permendikbudristek No. 30 of 2021 has an impact on the issue of refusal of sexual consent among the Muslim community. As a country that is imbued with religious beliefs, especially Islam, the Muslim community is of the view that the existence of sexual consent can injure the noble values of the One Godhead. The rolling issue of refusal can affect the effectiveness of the law. This study uses a socio-legal legal research method with a sociological approach and a conceptual approach. Sources of data using primary and secondary data with data collection techniques through interviews and survey methods. The data obtained from the survey were analyzed using a simple linear regression equation. The results showed that based on the results of linear regression analysis, the acceptance of the Muslim community towards sexual consent has a significant effect on the effectiveness of Permendikbud No. 30 of 2021. The form of acceptance of the Muslim community tends to be in the form of rejection of sexual consent regulated in Permendikbud No. 30 of 2021. Keywords: Legal Effectiveness, Sexual Consent, Muslim Society, Divine Values.